Sucralose decreases insulin sensitivity in healthy subjects: a randomized controlled trial - Romo-Romo, Alonso; Aguilar-Salinas, Carlos A; Brito-Córdova, Griselda X; Gómez-Díaz, Rita A; Almeda-Valdes, Paloma (The American journal of clinical nutrition, 2018)
Recently, the absence of metabolic effects from nonnutritive sweeteners has been questioned. The aim of this study was to evaluate the effects of sucralose consumption on glucose metabolism variables. We performed a randomized controlled trial involving healthy subjects without comorbidities and with a low habitual consumption of nonnutritive sweeteners (n = 33/group). The intervention consisted of sucralose consumption as 15% of Acceptable Daily Intake every day for 14 d using commercial sachets. The control group followed the same procedures without any intervention. The glucose metabolism variables (insulin sensitivity, acute insulin response to glucose, disposition index, and glucose effectiveness) were evaluated by using a 3-h modified intravenous-glucose-tolerance test before and after the intervention period. Individuals assigned to sucralose consumption showed a significant decrease in insulin sensitivity with a median (IQR) percentage change of −17.7% (−29.3% to −1.0%) in comparison to −2.8% (−30.7% to 40.6%) in the control group (P= 0.04). An increased acute insulin response to glucose from 577 mU · L-1· min (350–1040 mU · L-1· min) to 671 mU · L-1· min (376–1010 mU · L-1· min) (P = 0.04) was observed in the sucralose group for participants with adequate adherence. Sucralose may have effects on glucose metabolism, and our study complements findings previously reported in other trials. Further studies are needed to confirm the decrease in insulin sensitivity and to explore the mechanisms for these metabolic alterations. This trial was registered at www.clinicaltrials.gov as NCT02589002.